2018
DOI: 10.1016/j.chest.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

CPAP Adherence Predictors in a Randomized Trial of Moderate-to-Severe OSA Enriched With Women and Minorities

Abstract: ClinicalTrials.gov; No.: NCT00607893; URL: www.clinicaltrials.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 49 publications
1
25
0
1
Order By: Relevance
“…В свою очередь, коморбидность, как правило, нарастает с возрастом. В нашем исследовании, так же как и в ряде других [40][41][42][43][44][45][46][47][48][49][50], приверженные ПАП-терапии больные оказались старше по возрасту и имели более высокий ИАГ в сравнении с неприверженными. В многоцентровом исследовании J. Nogueira и соавт.…”
Section: Discussionunclassified
“…В свою очередь, коморбидность, как правило, нарастает с возрастом. В нашем исследовании, так же как и в ряде других [40][41][42][43][44][45][46][47][48][49][50], приверженные ПАП-терапии больные оказались старше по возрасту и имели более высокий ИАГ в сравнении с неприверженными. В многоцентровом исследовании J. Nogueira и соавт.…”
Section: Discussionunclassified
“… 14 In the USA, CPAP adherence was low in black subjects and lower socioeconomic residential areas 15 and was strongly associated with white race. 16 A Singaporean retrospective study showed that 50% of OSA patients continued CPAP therapy within five years. 17 A meta-analysis study indicated that the rate of CPAP adherence remains low over the last 20 years.…”
Section: Discussionmentioning
confidence: 99%
“…The substantial impact of allocation to therapy adherence has already been reported in other interventional trials by other groups involving sham CPAP devices and seems to be a universal phenomenon across sex, race, and ageboundaries. [23,[35][36][37] In the literature, this phenomenon is also referred to as the "Hawthorne effect", where individuals modify an aspect of their behavior in response to their awareness of being observed. Interestingly, in multivariable analyses, the treatment allocation was the strongest predictor of CPAP adherence within RCTs.…”
Section: Discussionmentioning
confidence: 99%